Physiological Mechanism of Enhancing Salt Stress Tolerance of Perennial Ryegrass by 24-Epibrassinolide - Wu, Wenli; Zhang, Qiang; Ervin, Erik. H.; Yang, Zhiping; Zhang, Xunzhong (Frontiers in Plant Science, 2017)
Brassinosteroids (BR) regulate plant tolerance to salt stress but the mechanisms underlying are not fully understood. This study was to investigate physiological mechanisms of 24-epibrassinolide (EBR)’s impact on salt stress tolerance in perennial ryegrass (Lolium perenne L.) The grass seedlings were treated with EBR at 0, 10, and 100 nM, and subjected to salt stress (250 mM NaCl). The grass irrigated with regular water without EBR served as the control. Salt stress increased leaf electrolyte leakage (EL), malondialdehyde (MDA) and reduced photosynthetic rate (Pn). Exogenous EBR reduced EL and MDA, increased Pn, chlorophyll content, and stomatal conductance (gs). The EBR applications also alleviated decline of superoxide dismutase (SOD) and catalase (CAT) and ascorbate peroxidase (APX) activity when compared to salt treatment alone. Salt stress increased leaf abscisic acid (ABA) and gibberellin A4 (GA4) content but reduced indole-3-acetic acid (IAA), zeatin riboside (ZR), isopentenyl adenosine (iPA), and salicylic acid (SA). Exogenous EBR at 10 nm and 100 nM increased ABA, and iPA content under salt stress. The EBR treatment at 100 nM also increased leaf IAA, ZR, JA, and SA. In addition, EBR treatments increased leaf proline and ions (K+, Mg2+, and Ca2+) content, and reduced Na+/K+ in leaf tissues. The results of this study suggest that EBR treatment may improve salt stress tolerance by increasing the level of selected hormones and antioxidant enzyme (SOD and CAT) activity, promoting accumulation of proline and ions (K+, Ca2+, and Mg2+) in perennial ryegrass.